1999
DOI: 10.3109/02770909909075409
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Asthma Symptom Severity Among Adult Asthmatics

Abstract: Contrary to what would be expected, smoking habits of asthmatics do not differ from those of the general population: approximately 30% of asthmatic patients smoke cigarettes. Although the relationship between smoking and the incidence of asthma has been well explored, little attention has been paid to documenting the relationship between smoking and asthma symptoms among adults with asthma. The objective of this study was to assess the association of cigarette smoking with asthma symptom severity. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
109
2
9

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 17 publications
9
109
2
9
Order By: Relevance
“…There was no significant difference in the number of patients who made unscheduled outpatient clinic visits for treatment within the previous three months, which is a gauge used to determine the recent aggravation of asthma symptoms. This differed from previous results possibly for reasons similar to the results obtained for oral corticosteroid use 3,5 . In the present study, current and former smokers used significantly more medication (i.e., leukotriene and theophylline) than non-smokers (p=0.03, p=0.02) presumably because smokers need more medication to control asthma symptoms.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…There was no significant difference in the number of patients who made unscheduled outpatient clinic visits for treatment within the previous three months, which is a gauge used to determine the recent aggravation of asthma symptoms. This differed from previous results possibly for reasons similar to the results obtained for oral corticosteroid use 3,5 . In the present study, current and former smokers used significantly more medication (i.e., leukotriene and theophylline) than non-smokers (p=0.03, p=0.02) presumably because smokers need more medication to control asthma symptoms.…”
Section: Discussioncontrasting
confidence: 57%
“…Asthmatic smokers are also more likely to require hospital care than asthmatic non-smokers [7][8][9][10] . Furthermore, asthma-related morbidity and mortality is higher among smokers Original Article than non-smokers 3,11 . Corticosteroids, especially inhaled corticosteroids, are currently the best anti-inflammatory therapy available for the treatment of asthma, and their use is recommended by the Global Initiative for Asthma (GINA) 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 The finding that active tobacco smoking is associated with significantly increased risk of asthma is also consistent with previous research. [53][54][55][56] However, active tobacco smoking is not a major confounder in this study because only a small proportion of women in India smoke tobacco (only 2.3% in the NFHS-2 sample). 4 A positive significant effect of biomass fuel use on asthma is also consistent with previous research linking cooking smoke to asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that exposure to tobacco smoke can increase the frequency and severity of asthmatic attacks (69)(70)(71), but some fail to link tobacco smoking to onset of asthma in adults (72,73). Smoking has been associated with airway hyperresponsiveness in a number of surveys as well as in clinical studies (27,(73)(74)(75)(76).…”
Section: Introductionmentioning
confidence: 99%